Positive electrode active material for all-solid-state battery, positive electrode for all-solid-state battery and all-solid-state battery including the same

By forming a coating of lithium-item carbon oxide and lithium titanium oxide on the surface of the positive electrode active material of lithium-ion battery, the reaction problem between the interface between the positive electrode active material and the electrolyte under the solid electrolyte of the sulfide matrix is ​​solved, and the improvement of battery interface characteristics and electrochemical performance are achieved.

JP2025511503AActive Publication Date: 2025-04-16LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024553484
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-12-02
Filing Date
2023-11-29
Publication Date
2025-04-16
Estimated Expiration
2043-11-29

AI Technical Summary

Technical Problem

Existing medium-sized and large lithium-ion batteries have high safety and performance requirements in high temperature and impact environments. When using sulfide matrix solid electrolytes, the reaction between the positive electrode active material and the electrolyte interface leads to a decrease in battery life.

Method used

A coating containing lithium-item carbon oxide and lithium titanium oxide is formed on the surface of the positive electrode active material. By adjusting the composition and thickness of the coating, the interface characteristics of the positive electrode active material and the solid electrolyte are improved and the side reaction is reduced.

Benefits of technology

It effectively reduces the interface resistance between the positive electrode active material and the solid electrolyte, suppresses side reactions, and improves the electrochemical performance and life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511503000001_ABST
    Figure 2025511503000001_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material for an all-solid-state battery, the positive electrode active material for an all-solid-state battery including a core capable of reversibly absorbing and releasing lithium ions and a coating layer formed on a surface of the core, the coating layer including a lithium carbon oxide represented by the following Chemical Formula 1 and a lithium titanium oxide represented by the following Chemical Formula 2, a positive electrode for an all-solid-state battery including the positive electrode active material for an all-solid-state battery and a sulfide-based solid electrolyte, a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode, the positive electrode including the positive electrode for an all-solid-state battery. [Chemical formula 1] Li a CO b In the above formula 1, a is 0 <a≦4、bは0<b≦4である; [Chemical formula 2] Li x Ti y O4 In the above Chemical Formula 2, x is 0.8≦x≦1.4, and y is 1.6≦y≦2.2.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0166647 dated December 2, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.

[0002] The present invention relates to a positive electrode active material for an all-solid-state battery, a positive electrode for an all-solid-state battery, and an all-solid-state battery including the same. [Background technology]

[0003] Lithium secondary batteries have been mainly used in small applications such as mobile devices and laptops, but recently research into them has expanded to medium and large applications such as energy storage systems (ESS) and electric vehicles (EV).

[0004] Unlike small batteries, medium and large lithium secondary batteries not only have harsh operating environments (e.g., temperature, impact) but also require the use of more batteries, so they need to be safe as well as have excellent performance and reasonable prices.

[0005] Most of the lithium secondary batteries currently on the market use an organic liquid electrolyte in which lithium salt is dissolved in an organic solvent, and therefore have potential risks of leakage, fire, and explosion. Therefore, the use of a solid electrolyte instead of the organic liquid electrolyte has been drawing attention as an alternative to overcome the safety issues.

[0006] An all-solid-state battery is composed of a positive electrode, a solid electrolyte, and a negative electrode. Sulfides and oxides can be used as the solid electrolyte for all-solid-state batteries, but sulfide-based solid electrolytes are the most promising materials from the viewpoint of lithium ion conductivity.

[0007] However, when using a sulfide-based solid electrolyte, a positive electrode active material coated with cobalt (Co) is generally not used in the positive electrode due to the reaction between cobalt and sulfur.

[0008] In addition, during the charge / discharge cycle of an all-solid-state battery, a reaction occurs at the interface between the positive electrode active material and the sulfide-based solid electrolyte, causing diffusion of components such as Co, P, and S at the interface, resulting in a decrease in life characteristics, and improvements to this issue are required. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Korean Patent Publication No. 2010-0120153 [Patent Document 2] Korean Patent Publication No. 2018-0076132 Summary of the Invention [Problem to be solved by the invention]

[0010] An object of the present invention is to provide a positive electrode active material for an all-solid-state battery, which can improve the interfacial resistance between the positive electrode active material layer and a solid electrolyte and suppress side reactions by forming a coating layer containing lithium carbon oxide and lithium titanium oxide on the positive electrode active material for an all-solid-state battery.

[0011] Another object of the present invention is to provide a positive electrode for an all-solid-state battery, comprising the positive electrode active material for an all-solid-state battery and a sulfide-based solid electrolyte.

[0012] It is still another object of the present invention to provide an all-solid-state battery having improved electrochemical properties and life characteristics by applying the positive electrode active material for an all-solid-state battery to a positive electrode. [Means for solving the problem]

[0013] One embodiment of the present invention provides a positive electrode active material for an all-solid-state battery, comprising a core capable of reversibly absorbing and releasing lithium ions and a coating layer formed on a surface of the core, the coating layer comprising a lithium carbon oxide represented by the following Chemical Formula 1 and a lithium titanium oxide represented by the following Chemical Formula 2: [Chemical formula 1]

[0014] Li a CO b In the above formula 1, a is 0 <a≦4、bは0<b≦4である; [Chemical formula 2]

[0015] Li x Ti y O4 In the above Chemical Formula 2, x is 0.8≦x≦1.4, and y is 1.6≦y≦2.2.

[0016] The coating layer may include a first coating layer and a second coating layer, respectively, from the center of the core to the surface of the core, the first coating layer may include the lithium carbon oxide represented by Chemical Formula 1, and the second coating layer may include the lithium titanium oxide represented by Chemical Formula 2.

[0017] The coating layer may be included in an amount of 0.1 to 10 parts by weight based on 100 parts by weight of the total positive electrode active material for an all-solid-state battery including both the core and the coating layer.

[0018] The lithium carbon oxide represented by Formula 1 may be included in an amount of 0.1 to 1.6 parts by weight based on 100 parts by weight of the total positive electrode active material for an all-solid-state battery including both the core and the coating layer.

[0019] The lithium titanium oxide represented by Formula 2 may be included in an amount of 0.1 to 1.5 parts by weight based on 100 parts by weight of the total positive electrode active material for an all-solid-state battery including both the core and the coating layer.

[0020] The lithium carbon oxide represented by Formula 1 and the lithium titanium oxide represented by Formula 2 contained in the coating layer may be contained in a weight ratio of 95:5 to 25:75.

[0021] The thickness ratio of the first coating layer to the second coating layer may be 20:80 to 80:20.

[0022] The first coating layer may have a thickness of 0.001 to 0.02 μm, and the second coating layer may have a thickness of 0.001 to 0.02 μm.

[0023] The lithium carbon oxide is Li2CO3, and the lithium titanium oxide is Li4Ti5O 12 It could be.

[0024] Another embodiment of the present invention provides a positive electrode for an all-solid-state battery, comprising the positive electrode active material for an all-solid-state battery and a sulfide-based solid electrolyte.

[0025] The sulfide-based solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiX (wherein X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n (where m and n are positive numbers, and Z is one of Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (where p and q are positive numbers, and M is one of P, Si, Ge, B, Al, Ga, and In), Li 7-x P.S. 6-x Cl x (where 0≦x≦2), Li 7-x P.S. 6-x Br x (where 0≦x≦2) and Li7-x P.S. 6-x I x (wherein, 0≦x≦2) may be one or more of the following.

[0026] The sulfide-based solid electrolyte may be an argyrodite-type solid electrolyte containing one or more selected from Li6PS5Cl, Li6PS5Br, and Li6PS5I.

[0027] Yet another embodiment of the present invention provides an all-solid-state battery comprising a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the positive electrode comprises the positive electrode for the all-solid-state battery. Effect of the Invention

[0028] According to the present invention, a coating layer is formed on a cathode active material for an all-solid-state battery, and the coating layer simultaneously contains lithium carbon oxide and lithium titanium oxide, thereby improving the interfacial resistance between the cathode active material and a solid electrolyte in the cathode active material layer of the all-solid-state battery and suppressing side reactions. In addition, by applying the cathode active material for an all-solid-state battery having the coating layer formed thereon to a cathode, the electrochemical properties and life properties of the all-solid-state battery including the same can be improved. [Brief description of the drawings]

[0029] [Figure 1] FIG. 1 is a schematic diagram of a positive electrode active material for an all-solid-state battery according to an embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic diagram of a positive electrode active material for an all-solid-state battery according to an embodiment of the present invention. [Diagram 3] 1 is an image showing an energy dispersive X-ray spectroscopy (EDAX) analysis result of a positive electrode active material for an all-solid-state battery according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Hereinafter, the embodiments of the present invention will be described in detail. Prior to this, the terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as meanings and concepts that correspond to the technical ideas of the present invention, based on the principle that the inventor can appropriately define the concepts of terms in order to best describe his / her invention. Therefore, since the configurations described in the embodiments described in this specification are merely the most preferred embodiments of the present invention and do not fully represent the technical ideas of the present invention, it should be understood that there are various equivalents and modifications that can replace them at the time of this application.

[0031] Throughout this specification, when a part is said to "comprise" certain elements, this means that it can further include other elements, rather than excluding other elements, unless specifically stated to the contrary.

[0032] Furthermore, descriptions that specify or limit components or add elements can be applied to all inventions unless otherwise specified, and are not limited to a particular invention.

[0033] Moreover, throughout the description and claims of this application, the singular includes the plural, unless specifically stated otherwise.

[0034] Furthermore, throughout the description of the invention and claims of this application, unless otherwise stated, "or" includes "and." Therefore, "including A or B" means all three cases of including A, including B, or including both A and B.

[0035] Additionally, all numerical ranges include the endpoints and all intermediate values ​​therebetween unless expressly stated to be excluded.

[0036] Throughout this specification the average particle size of the particles may be the median diameter (D50) measured, for example, using a laser particle size analyzer.

[0037] Hereinafter, a positive electrode active material for an all-solid-state battery according to one embodiment of the present invention will be described.

[0038] The present invention relates to a positive electrode active material for an all-solid-state battery, which can improve the electrochemical characteristics and life characteristics of the all-solid-state battery by improving the interfacial resistance between the positive electrode active material and a solid electrolyte and suppressing side reactions.

[0039] Generally, all-solid-state batteries, unlike general lithium secondary batteries, do not use a liquid electrolyte, and therefore contain a solid electrolyte not only in the solid electrolyte layer but also in the positive electrode active material layer.

[0040] At this time, in order to ensure stable ion conductivity, it is important that the positive electrode active material contained in the positive electrode active material layer and the solid electrolyte are in contact with each other effectively to form a high effective contact area, which acts as an important factor in improving the charge / discharge capacity and efficiency of the all-solid-state battery. In order to increase the effective contact area between the positive electrode active material and the solid electrolyte, a pressure of about 500 MPa or more is applied during the manufacturing process of the all-solid-state battery. In order to solve problems such as side reactions between the positive electrode active material and the solid electrolyte due to the pressure process, there have been attempts to improve this by introducing a lithium oxide coating layer containing elements such as B, Al, Zr, Nb, and W into the positive electrode active material.

[0041] However, even if a lithium oxide containing the above-mentioned element is introduced into the coating layer of the positive electrode active material, there is a problem that the interfacial resistance between the positive electrode active material and the solid electrolyte, which is required to improve the output of an all-solid-state battery containing a sulfide-based solid electrolyte and ensure long-life performance, is not significantly improved.

[0042] In order to solve the above problems, the present invention has been completed by forming a coating layer on the surface of a cathode active material for an all-solid-state battery, and by simultaneously including lithium carbon oxide and lithium titanium oxide in the coating layer, it has been confirmed that the interface resistance between the cathode active material and the solid electrolyte, particularly the sulfide-based solid electrolyte, can be reduced and side reactions can be suppressed in the cathode active material layer.

[0043] FIG. 1 is a schematic diagram showing a positive electrode active material for an all-solid-state battery according to one embodiment of the present invention.

[0044] Referring to FIG. 1, a positive electrode active material for an all-solid-state battery according to an embodiment of the present invention includes a core capable of reversibly absorbing and releasing lithium ions and a coating layer formed on a surface of the core, the coating layer including a lithium carbon oxide represented by the following Chemical Formula 1 and a lithium titanium oxide represented by the following Chemical Formula 2: [Chemical formula 1] Li a CO b In the above formula 1, a is 0 <a≦4、bは0<b≦4である; [Chemical formula 2] Li x Ti y O4 In the above Chemical Formula 2, x is 0.8≦x≦1.4, and y is 1.6≦y≦2.2.

[0045] The positive electrode active material for an all-solid-state battery contains the lithium carbon oxide represented by Chemical Formula 1 in the coating layer formed on the surface, thereby suppressing an increase in electrochemical interface contact resistance caused by contraction and expansion of the positive electrode active material during charging and discharging of the all-solid-state battery. In addition, the positive electrode active material contains the lithium titanium oxide represented by Chemical Formula 2, thereby preventing an excessively thick solid electrolyte interface film from being formed on the surface of the positive electrode active material and controlling thermal runaway factors, thereby improving the battery chemical characteristics and stability of the all-solid-state battery, and allowing smooth inflow and outflow of Li ions to provide the battery with rapid charge and discharge characteristics.

[0046] The lithium carbon oxide represented by the formula 1 and the lithium titanium oxide represented by the formula 2 are not limited to the formulas, and may be expressed in the form of a multiple of the molar number within a range satisfying the molar ratio of each atom.

[0047] For example, in the case of the lithium titanium oxide represented by the formula 2, the number of moles of oxygen is fixed to 4, but the formula 2 is not limited thereto and can be expressed in the form of a multiple satisfying the molar ratio of each atom. If the number of moles of oxygen is 12, the formula 2 is Li 3x Ti 3y O 12 It can also be shown as:

[0048] In one embodiment of the present invention, the lithium carbon oxide contained in the coating layer of the positive electrode active material for the all-solid-state battery may be, for example, Li2CO3, and the lithium titanium oxide may be Li4Ti5O 12 It could be.

[0049] Referring to FIG. 2, in one embodiment of the present invention, the coating layer may include a first coating layer and a second coating layer in order from the center of the core to the surface of the core, the first coating layer may include the lithium carbon oxide represented by Chemical Formula 1, and the second coating layer may include the lithium titanium oxide represented by Chemical Formula 2.

[0050] That is, the first coating layer close to the surface of the positive electrode active material contains the lithium carbon oxide represented by Chemical Formula 1, thereby solving the problem of an increase in interfacial resistance between the positive electrode active material and the solid electrolyte due to a decrease in the mechanical contact area. The second coating layer formed on the first coating layer and positioned at the outermost corner of the positive electrode active material contains the lithium titanium oxide represented by Chemical Formula 2, thereby suppressing direct interfacial contact between the positive electrode active material and the solid electrolyte. + The ingress and egress of ions other than ions is restricted, and the problem of resistance increase due to electrochemical side reactions can be solved. If, unlike the above embodiment, the first coating layer contains the lithium titanium oxide represented by Chemical Formula 2 and the second coating layer contains the lithium carbon oxide represented by Chemical Formula 1, it may be difficult for each coating layer to properly perform the role described above, and a problem of a significant increase in interfacial resistance between the positive electrode active material and the solid electrolyte may occur.

[0051] In one embodiment of the present invention, the coating layer is preferably included in an amount of 0.1 to 10 parts by weight based on 100 parts by weight of the total positive electrode active material for an all-solid-state battery including both the core and the coating layer.

[0052] If the content of the coating layer is less than 0.1 parts by weight based on 100 parts by weight of the total positive electrode active material for an all-solid-state battery, there may be a problem that the surface of the positive electrode active material is not partially coated, or a complete coating layer is not formed. If the content of the coating layer exceeds 10 parts by weight, there may be a problem that the gap between the positive electrode active material and the solid electrolyte increases, resulting in an increase in interface resistance.

[0053] In one embodiment of the present invention, the lithium carbon oxide represented by Chemical Formula 1 may be included in an amount of 0.1 to 1.6 parts by weight based on 100 parts by weight of the total positive electrode active material for an all-solid-state battery including both the core and the coating layer, and may be included in an amount of, for example, 0.1 parts by weight or more, 0.2 parts by weight or more, 0.3 parts by weight or more, 0.4 parts by weight or more, 0.5 parts by weight or more, 0.6 parts by weight or more, 0.7 parts by weight or more, 0.8 parts by weight or more, or 0.9 parts by weight or more, or may be 1.6 parts by weight or less, 1.5 parts by weight or less, 1.4 parts by weight or less, 1.3 parts by weight or less, 1.2 parts by weight or less, or 1.1 parts by weight or less.

[0054] In one embodiment of the present invention, when the coating layer formed on the surface of the cathode active material for the all-solid-state battery is formed of a first coating layer and a second coating layer from the center of the core toward the surface of the cathode active material, and the lithium carbon oxide represented by Chemical Formula 1 is contained in the first coating layer, the lithium carbon oxide represented by Chemical Formula 1 may be contained in an amount of 0.1 to 1.6 parts by weight based on 100 parts by weight of the total cathode active material for the all-solid-state battery including the core, the first coating layer, and the second coating layer.

[0055] If the content of the lithium carbon oxide represented by the formula 1 is less than 0.1 parts by weight, there may be a problem that the surface of the positive active material is not partially coated, and a problem that a complete coating layer is not formed may occur. If the content exceeds 1.6 parts by weight, there may be a problem that the gap between the positive active material and the solid electrolyte increases, and the interface resistance increases. Therefore, it is preferable that the content of the lithium carbon oxide represented by the formula 1 is within the above range.

[0056] In one embodiment of the present invention, the lithium titanium oxide represented by Chemical Formula 2 may be included in an amount of 0.1 to 1.5 parts by weight based on 100 parts by weight of the total positive electrode active material for an all-solid-state battery including both the core and the coating layer, and may be included in an amount of, for example, 0.1 parts by weight or more, 0.2 parts by weight or more, 0.3 parts by weight or more, 0.4 parts by weight or more, 0.5 parts by weight or more, 0.6 parts by weight or more, 0.7 parts by weight or more, 0.8 parts by weight or more, or 0.9 parts by weight or more, or may be 1.5 parts by weight or less, 1.4 parts by weight or less, 1.3 parts by weight or less, 1.2 parts by weight or less, or 1.1 parts by weight or less.

[0057] In one embodiment of the present invention, when the coating layer formed on the surface of the cathode active material for the all-solid-state battery is formed of a first coating layer and a second coating layer from the center of the core toward the surface of the cathode active material, and the lithium titanium oxide represented by Chemical Formula 2 is contained in the second coating layer, the lithium titanium oxide represented by Chemical Formula 2 may be contained in an amount of 0.1 to 1.5 parts by weight based on 100 parts by weight of the total cathode active material for the all-solid-state battery including the core, the first coating layer, and the second coating layer.

[0058] If the content of the lithium titanium oxide represented by the formula 2 is less than 0.1 parts by weight, there may be a problem that the surface of the positive active material is not partially coated, and a problem that a complete coating layer is not formed may occur. If the content exceeds 1.5 parts by weight, there may be a problem that the gap between the positive active material and the solid electrolyte increases, and the interface resistance increases. Therefore, it is preferable that the content of the lithium titanium oxide represented by the formula 2 is within the above range.

[0059] In addition, in one embodiment of the present invention, the lithium carbon oxide represented by Chemical Formula 1 and the lithium titanium oxide represented by Chemical Formula 2 contained in the coating layer of the positive electrode active material for the all-solid-state battery may be contained in a weight ratio of 95:5 to 25:75.

[0060] For example, the lithium carbon oxide represented by Chemical Formula 1 and the lithium titanium oxide represented by Chemical Formula 2 may be in a weight ratio of 95:5, 16:1, 90:10, 85:15, 5:1, 80:20, 75:25, 70:30, 65:35, 60:40, 55:45, 50:50, 45:55, 40:60, 35:65, 30:70, or 25:75.

[0061] In the positive electrode active material for an all-solid-state battery according to the present invention, if the content range of the lithium carbon oxide represented by Chemical Formula 1 is less than 25 parts by weight based on 100 parts by weight of the total of the lithium carbon oxide represented by Chemical Formula 1 and the lithium titanium oxide represented by Chemical Formula 2, a problem may occur in that the first coating layer containing the lithium carbon oxide directly contacts the solid electrolyte, and if it exceeds 95 parts by weight, a side reaction may occur due to the lithium carbon oxide being mixed into the second coating layer containing the lithium titanium oxide, resulting in an increase in the interfacial resistance between the positive electrode active material and the solid electrolyte.

[0062] In the positive electrode active material for an all-solid-state battery according to the present invention, if the content range of the lithium titanium oxide represented by Chemical Formula 2 is less than 5 parts by weight based on 100 parts by weight of the total of the lithium carbon oxide represented by Chemical Formula 1 and the lithium titanium oxide represented by Chemical Formula 2, the lithium carbon oxide may be mixed into the second coating layer containing the lithium titanium oxide, causing a side reaction, resulting in an increase in the interfacial resistance between the positive electrode active material and the solid electrolyte. If the content range exceeds 75 parts by weight, the first coating layer containing the lithium carbon oxide may directly contact the solid electrolyte.

[0063] In an embodiment of the present invention, a thickness ratio of the first coating layer to the second coating layer may be 20:80 to 80:20.

[0064] Furthermore, within the range satisfying the thickness ratio, the thickness of the first coating layer may be 0.001 to 0.02 μm, and the thickness of the second coating layer may be 0.001 to 0.02 μm.

[0065] In the cathode active material for an all-solid-state battery according to the present invention, when the first coating layer and the second coating layer formed on the surface have the above-mentioned thickness ratio and thickness range, a side reaction between the cathode active material and a sulfide-based solid electrolyte can be substantially reduced and / or effectively minimized or effectively blocked.

[0066] The core contained in the positive electrode active material for the all-solid-state battery is not particularly limited as long as it is a lithium composite oxide material capable of reversibly absorbing and releasing lithium ions. For example, it may contain one or more composite oxides of metals such as cobalt, manganese, nickel, iron, or a combination thereof; and lithium.

[0067] More specifically, the positive electrode active material may be a compound represented by any one of the following chemical formulas: a A 1-b R b D2 (wherein, 0.90≦a≦1.8 and 0≦b≦0.5); Li a E 1-b R b O 2-c D c (wherein 0.90≦a≦1.8, 0≦b≦0.5, and 0≦c≦0.05); LiE 2-b R b O 4-c D c (wherein, 0≦b≦0.5 and 0≦c≦0.05); Li a Ni 1-b-c Co b R c D α(wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2); Li a Ni 1-b-c Co b R c O 2-α Z α (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Co b R c O 2-α Z2 (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b R c D α (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2); Li a Ni 1-b-c Mn b R c O 2-α Z α (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b R c O 2-α Z2 (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni b E c G d O2 (wherein 0.90≦a≦1.8, 0≦b≦0.9, 0≦c≦0.5, and 0.001≦d≦0.1); Li a Ni b Co c Mn d G e O2 (wherein 0.90≦a≦1.8, 0≦b≦0.9, 0≦c≦0.5, 0≦d≦0.5, and 0≦e≦0.1); Li a NiG bO2 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1); Li a CoG b O2 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1); Li a MnG b O2 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1); Li a Mn2G b O4 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiTO2; LiNiVO4; Li (3-f) J2(PO4)3(0≦f≦2);Li (3-f) Fe2(PO4)3(0≦f≦2); and LiFePO4.

[0068] In the above chemical formula, A is Ni, Co, Mn or a combination thereof; R is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements or a combination thereof; D is O, F, S, P or a combination thereof; E is Co, Mn or a combination thereof; Z is F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q is Ti, Mo, Mn or a combination thereof; T is Cr, V, Fe, Sc, Y or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu or a combination thereof.

[0069] According to another aspect, there is provided a positive electrode for an all-solid-state battery, comprising the positive electrode active material for an all-solid-state battery according to the above-mentioned embodiment of the present invention.

[0070] In one embodiment, the all-solid-state battery positive electrode can include the all-solid-state battery positive electrode active material and a sulfide-based solid electrolyte.

[0071] At this time, since the positive electrode active material for the all-solid-state battery is the same as the content described above, hereinafter, regarding the positive electrode active material contained in the positive electrode for the all-solid-state battery according to the present invention, detailed description in this specification will be omitted hereinafter.

[0072] In one embodiment of the present invention, the sulfide-based solid electrolyte contained in the positive electrode for the all-solid-state battery may be represented by the following Chemical Formula 3. [Chemical Formula 3]

[0073] Li k M 2 l S m X 2 n In Chemical Formula 3, M 2 is Sn, Mg, Ba, B, Al, Ga, In, Si, Ge, Pb, N, P, As, Sb, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W, or La, and X 2 is F, Cl, Br, I, Se, Te, or O, and 0 < k ≦ 6, 0 < l ≦ 6, 0 < m ≦ 6, and 0 ≦ n ≦ 6.

[0074] For example, in Chemical Formula 3, M 2 may be B, Si, Ge, P, or N.

[0075] For example, in Chemical Formula 3, X 2 may be F, Cl, Br, I, or O.

[0076] For example, the sulfide-based solid electrolyte represented by Chemical Formula 3 is Li2S-P2S5, Li2S-P2S5-LiX, X is a halogen element, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n, m and n are positive numbers, Z is one of Ge, Zn or Ga, Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q , p, q are positive numbers, M is one of P, Si, Ge, B, Al, Ga, In, Li 7-x P.S. 6-x Cl x , 0≦x≦2, Li 7-x P.S. 6-x Br x , 0≦x≦2, and Li 7-x P.S. 6-x I x , 0≦x≦2.

[0077] Preferably, the sulfide-based solid electrolyte may be an argyrodite-type solid electrolyte containing one or more selected from Li6PS5Cl, Li6PS5Br, and Li6PS5I.

[0078] In an embodiment of the present invention, the positive electrode for the all-solid-state battery may further include a conductive material and a binder.

[0079] The conductive material is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and examples of the conductive material that can be used include graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, etc.; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives. The conductive material may be contained in an amount of about 0.01 to 10 parts by weight, or 0.01 to 5 parts by weight, or 0.01 to 3 parts by weight based on 100 parts by weight of the total positive electrode.

[0080] The binder is a component that is added in consideration of the binding property of a positive electrode active material, a sulfide-based solid electrolyte, and a conductive material for the positive electrode for the all-solid-state battery, and any polymer binder known to be usable for forming an electrode in the technical field to which the present invention belongs may be used without any particular limitation.

[0081] Examples of such polymer binders include acrylic binders, polyvinylidene fluoride (PVDF) binders, polytetrafluoroethylene (PTFE) binders, butadiene rubber binders such as nitrile butadiene rubber (NBR), etc., and of course, various other polymer binders can be used. The binder may be included in an amount of about 0.01 to 10 parts by weight, or 0.01 to 5 parts by weight, or 0.01 to 3 parts by weight, based on 100 parts by weight of the total positive electrode.

[0082] A positive electrode for an all-solid-state battery according to an embodiment of the present invention may include a current collector and a positive electrode active material layer formed on at least one surface of the current collector, and the positive electrode active material layer may include the positive electrode active material, a sulfide-based solid electrolyte, a conductive material, and a binder.

[0083] The positive electrode may be manufactured according to a method widely known in the art and is not limited to a specific manufacturing method. For example, the positive electrode may be manufactured by mixing the positive electrode active material, the sulfide-based solid electrolyte, the conductive material, the binder, etc. in a solvent to manufacture a positive electrode mixture in the form of a slurry, and applying the positive electrode mixture to a positive electrode current collector.

[0084] The positive electrode current collector is generally prepared to a thickness of 3 to 500 μm. Such a positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. The current collector can also be formed with fine irregularities on its surface to increase the adhesive force of the positive electrode active material, and can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0085] In addition to the above-mentioned positive electrode active material, sulfide-based solid electrolyte, conductive material, and binder, the positive electrode may further include additives such as a filler, a coating agent, a dispersant, an ion-conductive auxiliary, etc. As the filler, coating agent, dispersant, ion-conductive auxiliary, etc., known materials generally used in electrodes of all-solid-state secondary batteries may be used.

[0086] The thickness of the positive electrode may be, for example, 70 to 150 μm.

[0087] Another embodiment of the present invention provides an all-solid-state battery including a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode, the positive electrode being the positive electrode for the all-solid-state battery described above.

[0088] The positive electrode contained in the all-solid-state battery has been described in detail above, and therefore, the negative electrode and solid electrolyte contained in the all-solid-state battery will be described in detail below.

[0089] The solid electrolyte layer disposed between the positive electrode and the negative electrode may include, for example, a sulfide-based solid electrolyte. The sulfide-based solid electrolyte may be the same or different from the sulfide-based solid electrolyte included in the positive electrode.

[0090] For specific details regarding the sulfide-based solid electrolyte, see the above-mentioned positive electrode section.

[0091] The elastic modulus of the solid electrolyte, i.e., Young's modulus, is, for example, 35 GPa or less, 30 GPa or less, 27 GPa or less, 25 GPa or less, or 23 GPa or less. The elastic modulus of the solid electrolyte, i.e., Young's modulus, is, for example, 10 to 35 GPa, 15 to 35 GPa, 15 to 30 GPa, or 15 to 25 GPa. When the solid electrolyte has an elastic modulus in such a range, the solid electrolyte can be more easily pressed and / or sintered.

[0092] The solid electrolyte layer further includes, for example, a binder. The binder included in the solid electrolyte layer is, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but is not limited thereto, and any binder used as a binder in the relevant technical field is possible. The binder of the solid electrolyte layer may be the same or different from the binder of the positive electrode active material layer and the negative electrode active material layer.

[0093] Next, the negative electrode of the all-solid-state battery can include a negative electrode current collector and a negative electrode active material layer.

[0094] The thickness of the negative electrode active material layer is, for example, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less of the thickness of the positive electrode active material layer. The thickness of the negative electrode active material layer is, for example, 1 μm to 20 μm, 2 μm to 10 μm, or 3 μm to 7 μm. If the thickness of the negative electrode active material layer is too thin, lithium dendrites formed between the negative electrode active material layer and the negative electrode current collector collapse the negative electrode active material layer, making it difficult to improve the cycle characteristics of the all-solid-state battery. If the thickness of the negative electrode active material layer is excessively increased, the energy density of the all-solid-state battery decreases, the internal resistance of the all-solid-state battery due to the negative electrode active material layer increases, and it is difficult to improve the cycle characteristics of the all-solid-state battery.

[0095] The negative electrode active material layer contains, for example, a negative electrode active material that forms an alloy or compound with lithium.

[0096] The negative electrode active material contained in the negative electrode active material layer has, for example, a particulate form. The average particle size of the negative electrode active material having a particulate form is, for example, 4 μm or less, 3 μm or less, 2 μm or less, 1 μm or less, or 900 nm or less. The average particle size of the negative electrode active material having a particulate form is, for example, 10 nm to 4 μm or less, 10 nm to 3 μm or less, 10 nm to 2 μm or less, 10 nm to 1 μm or less, or 10 nm to 900 nm or less. When the negative electrode active material has an average particle size in such a range, reversible absorbing and / or desorbing of lithium during charging and discharging can be more easily performed. The average particle size of the negative electrode active material is, for example, a volume-equivalent median diameter (D50) measured using a laser type particle size distribution meter.

[0097] The negative electrode active material included in the negative electrode active material layer may include, for example, at least one selected from a carbon-based negative electrode active material and a metal or semimetal negative electrode active material.

[0098] The carbon-based negative electrode active material is, in particular, amorphous carbon. Examples of amorphous carbon include, but are not limited to, carbon black (CB), acetylene black (AB), furnace black (FB), ketjen black (KB), graphene, etc., and any material that is classified as amorphous carbon in the art can be used. Amorphous carbon is carbon that has no crystallinity or has very low crystallinity, and is classified as crystalline carbon or graphite-based carbon.

[0099] The metal or semi-metal negative electrode active material includes, but is not limited to, at least one selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn), and may be any metal or semi-metal negative electrode active material that forms an alloy or compound with lithium in the art. For example, nickel (Ni) is not a metal negative electrode active material because it does not form an alloy with lithium.

[0100] The negative electrode active material layer includes one of these negative electrode active materials or a mixture of a plurality of different negative electrode active materials. For example, the negative electrode active material layer includes only amorphous carbon, or includes one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). Alternatively, the negative electrode active material layer includes a mixture of amorphous carbon and one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). The weight ratio of the mixture of amorphous carbon and silver (Ag) is, for example, 10:1 to 1:2, 5:1 to 1:1, or 4:1 to 2:1, but is not necessarily limited to such ranges and is selected according to the required characteristics of the all-solid-state battery. When the negative electrode active material has such a composition, the cycle characteristics of the all-solid-state battery are further improved.

[0101] The negative electrode active material contained in the negative electrode active material layer includes, for example, a mixture of first particles made of amorphous carbon and second particles made of a metal or a metalloid. The metal or metalloid includes, for example, gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn), etc. The metalloid is also a semiconductor. The content of the second particles is 8 to 60 wt%, 10 to 50 wt%, 15 to 40 wt%, or 20 to 30 wt%, based on the total weight of the mixture. When the second particles have a content in such a range, for example, the cycle characteristics of the all-solid-state battery are further improved.

[0102] The negative electrode active material layer includes, for example, a binder. The binder is, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc., but is not necessarily limited thereto, and any binder used as a binder in the relevant technical field is possible. The binder may be composed of a single binder or a plurality of different binders.

[0103] By including a binder in the negative electrode active material layer, the negative electrode active material layer is stabilized on the negative electrode current collector. In addition, cracks in the negative electrode active material layer are suppressed despite changes in volume and / or relative position of the negative electrode active material layer during charging and discharging. For example, when the negative electrode active material layer does not include a binder, the negative electrode active material layer can be easily separated from the negative electrode current collector. The portion where the negative electrode active material layer is separated from the negative electrode current collector is exposed and comes into contact with the solid electrolyte layer, increasing the possibility of short circuit. The negative electrode active material layer is prepared, for example, by applying a slurry in which materials constituting the negative electrode active material layer are dispersed onto the negative electrode current collector and drying the slurry. By including a binder in the negative electrode active material layer, stable dispersion of the negative electrode active material in the slurry is possible. For example, when applying the slurry onto the negative electrode current collector by screen printing, clogging of the screen (for example, clogging due to agglomerates of the negative electrode active material) can be suppressed.

[0104] The negative electrode current collector is made of, for example, a material that does not react with lithium, i.e., does not form both an alloy and a compound. The material constituting the negative electrode current collector is, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), etc., but is not necessarily limited thereto, and any material used as an electrode current collector in the relevant technical field is possible. The negative electrode current collector can be made of one of the above-mentioned metals, or an alloy or coating material of two or more metals. The negative electrode current collector is, for example, in the form of a plate or foil.

[0105] The negative electrode active material layer can further contain additives used in conventional all-solid-state batteries, such as a filler, a dispersant, an ion conductive material, and the like.

[0106] An all-solid-state battery can be produced, for example, by producing a positive electrode, a negative electrode, and a solid electrolyte layer, and then laminating these layers.

[0107] The present invention provides a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.

[0108] Specific examples of the device include, but are not limited to, power tools that are driven by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.

[0109] Specific examples of the present invention are presented below. However, the examples described below are merely for the purpose of specifically illustrating or explaining the present invention, and the present invention is not limited thereby. Furthermore, the contents not described here can be sufficiently inferred by a person skilled in the art, and therefore the description thereof will be omitted.

[0110] Production Example 1: Production of positive electrode active material for all-solid-state batteries (1) Li2CO3 and Ni 0.8 Co 0.1 Mn 0.1 The mixture was mixed with (OH)2 in a mixer in a weight ratio of 1.1:1 to form a reaction mixture, which was then placed in a stainless steel crucible and subjected to a primary heat treatment at 600°C in an air atmosphere for 6 hours to form a plastic mixture, which was then cooled. The mixture was then crushed and sieved, and the crushed plastic mixture was placed in an aluminum crucible and subjected to a secondary heat treatment at 800°C in an air atmosphere for 10 hours to produce a cathode active material.

[0111] (2) The cathode active material prepared in (1) was charged into a tube furnace having an inner diameter of 50 mm and a length of 1,000 mm, and then heat-treated at 700°C to prepare a cathode active material having a first coating layer including 0.5 parts by weight of lithium carbon oxide, Li2CO3, based on the total weight of the cathode active material.

[0112] (3) Next, titanium (IV) isopropoxide and lithium ethoxide were added as precursors of lithium titanium oxide in a stoichiometric ratio and dissolved in ethanol to obtain Li4Ti5O 12 The positive electrode active material having the first coating layer formed thereon is mixed with the Li4Ti5O 12 The mixed solution was mixed for 24 hours using a Lab Blender (Waring), and then vacuum dried to remove the ethanol solvent. The mixed solution was then placed in a tube furnace with an inner diameter of 50 mm and a length of 1,000 mm, and heat-treated at 400°C for 4 hours to produce lithium titanium oxide, Li4Ti5O 12 A positive electrode active material for an all-solid-state battery having a second coating layer including 0.1 parts by weight based on the total weight of the positive electrode active material was prepared.

[0113] Production Example 2: Production of positive electrode active material for all-solid-state batteries Lithium titanium oxide Li4Ti5O 12 A positive electrode active material for an all-solid-state battery was prepared in the same manner as in Preparation Example 1, except that a second coating layer containing 1.5 parts by weight of the compound based on the total weight of the positive electrode active material was formed.

[0114] Production Example 3: Production of positive electrode active material for all-solid-state batteries A positive electrode active material for an all-solid-state battery was prepared in the same manner as in Preparation Example 1, except that in step (1) of Preparation Example 1, a first heat treatment was performed at 650°C to form a first coating layer containing 0.1 parts by weight of Li2CO3, which is a lithium carbon oxide, based on the total weight of the positive electrode active material.

[0115] Production Example 4: Production of positive electrode active material for all-solid-state batteries A positive electrode active material for an all-solid-state battery was prepared in the same manner as in Preparation Example 1, except that in step (1) of Preparation Example 1, a first heat treatment was performed at 700°C to form a first coating layer containing 1.6 parts by weight of Li2CO3, which is a lithium carbon oxide, based on the total weight of the positive electrode active material.

[0116] Comparative Manufacturing Example 1: Manufacturing of positive electrode active material for all-solid-state batteries (1) Li2CO3 and Ni 0.8 Co 0.1 Mn 0.1 The mixture was mixed with (OH)2 in a mixer at a weight ratio of 1.1:1 to form a reaction mixture, which was then placed in a stainless steel crucible and subjected to a primary heat treatment at 600°C in an air atmosphere for 5 hours to form a plastic mixture, which was then cooled. The mixture was then crushed and sieved, and the crushed plastic mixture was placed in an aluminum crucible and subjected to a secondary heat treatment at 800°C in an air atmosphere for 10 hours to prepare a positive electrode active material. The prepared positive electrode active material was placed in a tube furnace with an inner diameter of 50 mm and a length of 1,000 mm and subjected to a heat treatment at 700°C to completely remove lithium carbon oxide Li2CO3.

[0117] (2) Next, titanium (IV) isopropoxide and lithium ethoxide were added as precursors of lithium titanium oxide in a stoichiometric ratio and dissolved in ethanol to obtain Li4Ti5O 12 The positive electrode active material produced in (1) is added to the Li4Ti5O 12 The mixed solution was mixed for 24 hours using a Lab Blender (Waring), and then vacuum dried to remove the ethanol solvent. The mixed solution was then placed in a tube furnace with an inner diameter of 50 mm and a length of 1,000 mm, and heat-treated at 400°C for 4 hours to produce lithium titanium oxide, Li4Ti5O 12In the present invention, a positive electrode active material for an all-solid-state battery was prepared by forming only a coating layer containing 0.1 parts by weight of the above based on the total weight of the positive electrode active material.

[0118] Comparative Manufacturing Example 2: Manufacturing of positive electrode active material for all-solid-state batteries (1) Li2CO3 and Ni 0.8 Co 0.1 Mn 0.1 The mixture was mixed with (OH)2 in a mixer at a weight ratio of 1.1:1 to form a reaction mixture, which was then placed in a stainless steel crucible and subjected to a primary heat treatment at 600°C in an air atmosphere for 5 hours to form a plastic mixture, which was then cooled. The mixture was then crushed and sieved, and the crushed plastic mixture was placed in an aluminum crucible and subjected to a secondary heat treatment at 800°C in an air atmosphere for 10 hours to produce a positive electrode active material.

[0119] (2) The cathode active material prepared in (1) was charged into a tube furnace having an inner diameter of 50 mm and a length of 1,000 mm, and then heat-treated at 700°C to prepare a cathode active material for an all-solid-state battery having only a coating layer containing 0.5 parts by weight of lithium carbon oxide, Li2CO3, based on the total weight of the cathode active material.

[0120] Comparative Manufacturing Example 3: Manufacturing of positive electrode active material for all-solid-state batteries Lithium titanium oxide Li4Ti5O 12 A positive electrode active material for an all-solid-state battery was prepared in the same manner as in Preparation Example 1, except that a second coating layer containing 0.01 parts by weight of the positive electrode active material was formed.

[0121] Comparative Production Example 4: Production of positive electrode active material for all-solid-state batteries Lithium titanium oxide Li4Ti5O 12 A positive electrode active material for an all-solid-state battery was prepared in the same manner as in Preparation Example 1, except that a second coating layer containing 2.0 parts by weight of the positive electrode active material was formed.

[0122] Comparative Production Example 5: Production of positive electrode active material for all-solid-state batteries A positive electrode active material for an all-solid-state battery was prepared in the same manner as in Preparation Example 1, except that a first coating layer containing 2.0 parts by weight of lithium carbon oxide Li2CO3 based on the total weight of the positive electrode active material was formed.

[0123] Comparative Production Example 6: Production of positive electrode active material for all-solid-state batteries (1) In the same manner as in Comparative Production Example 1, lithium titanium oxide Li4Ti5O 12 A positive electrode active material for an all-solid-state battery having a first coating layer including 0.1 parts by weight based on the total weight of the positive electrode active material was prepared.

[0124] (2) Li2CO3 was added to ethanol to prepare a Li2CO3 solution, and the cathode active material prepared in (1) was added to the solution to prepare a mixed solution, which was then vacuum dried to remove the solvent ethanol, thereby preparing a cathode active material for an all-solid-state battery having a second coating layer containing 0.5 parts by weight of Li2CO3, a lithium carbon oxide, based on the total weight of the cathode active material.

[0125] Example 1: Preparation of positive electrode for all-solid-state battery (1) A cathode active material (78 parts by weight) prepared in Preparation Example 1, a sulfide-based solid electrolyte (19.5 parts by weight) of Li6PS5Cl, and a conductive material (vapor grown carbon nanofibers (VGCF TM 1.5 parts by weight of polytetrafluoroethylene (PTFE) as a binder (1 part by weight, Showa Denko Co., Ltd.) were added to a container and mixed at 5,000 rpm for 1 minute using a Lab Blender (Waring Co., Ltd.) without using a separate solvent. Next, a shear force of 100 N was applied to the mixture to perform high shear mixing (PBV-0.1L, Irie Shokai Co., Ltd.) to prepare a cathode slurry.

[0126] (2) The prepared positive electrode slurry was used to prepare a free-standing film using a Two Roll Mill MR-3 (Inoue Co., Ltd.) Then, the film was placed on one side of an aluminum current collector having a thickness of 15 μm and pressed to prepare a positive electrode for an all-solid-state battery.

[0127] Examples 2 to 4: Production of positive electrodes for all-solid-state batteries Positive electrodes for all-solid-state batteries according to Examples 2 to 4 were produced in the same manner as in Example 1, except that the positive electrode active materials produced in Examples 2 to 4 were used instead of the positive electrode active material produced in Example 1.

[0128] Comparative Examples 1 to 6: Production of positive electrodes for all-solid-state batteries Positive electrodes for all-solid-state batteries according to Comparative Examples 1 to 6 were manufactured in the same manner as in Example 1, except that the positive electrode active materials manufactured in Comparative Preparation Examples 1 to 6 were used instead of the positive electrode active material manufactured in Preparation Example 1.

[0129] Experimental example 1: EDX (Energy dispersive X-ray spectroscopy) analysis of positive electrode active material for all-solid-state batteries In order to measure the oxide components contained in the coating layer of the positive electrode active material for an all-solid-state battery prepared in Preparation Example 1, an EDX (Energy dispersive X-ray spectroscopy) experiment was performed, and the results are shown in Figure 3. The EDX measurement device used was a JEOL JSM7900F.

[0130] As shown in FIG. 3, in the case of the positive electrode active material for an all-solid-state battery prepared according to Preparation Example 1, it was found that the coating layer formed on the surface of the positive electrode active material simultaneously contained carbon and titanium elements.

[0131] Experimental Example 2: Evaluation of initial discharge capacity and life characteristics The initial discharge capacity and life characteristics of the all-solid-state batteries including the positive electrodes according to Examples 1 to 4 and Comparative Examples 1 to 6 were evaluated.

[0132] The all-solid-state battery uses lithium metal having a thickness of 40 μm as the negative electrode, and a Li6PS5Cl solid electrolyte membrane having a thickness of 50 μm is interposed between the positive electrode and the negative electrode manufactured in Examples 1 to 4 and Comparative Examples 1 to 6. The battery is pressurized at a pressure of 500 MPa, and is operated at a driving pressure of 3 MPa and 5 mAh / cm. 2 The cell was prepared in the form of a jig cell having a capacity.

[0133] (1) Evaluation of initial discharge capacity of all-solid-state batteries The charge / discharge characteristics of the all-solid-state batteries including the positive electrodes according to Examples 1 to 4 and Comparative Examples 1 to 6 were evaluated by the following charge / discharge test.

[0134] The battery was charged at a rate of 0.1 C until the voltage reached 4.25 V (vs. Li), and then cut off at a rate of 0.05 C while maintaining the voltage at 4.25 V (vs. Li). The battery was then discharged at a rate of 0.1 C until the voltage reached 3.0 V (vs. Li) (1 st The results are shown in Table 1 below.

[0135] Referring to Table 1, it was confirmed that the all-solid-state batteries according to Examples 1 to 4 exhibited higher reversible capacity and energy density than the all-solid-state batteries according to Comparative Examples 1 to 6. In particular, it was found that when the positive electrode active material did not include a first coating layer (Comparative Example 1) or the content of lithium carbon oxide in the first coating layer exceeded a certain range (Comparative Example 5), the reversible capacity and energy density were significantly reduced compared to the all-solid-state batteries according to the Examples.

[0136] (2) Evaluation of life characteristics of all-solid-state batteries The life characteristics of the all-solid-state batteries including the positive electrodes according to Examples 1 to 4 and Comparative Examples 1 to 6 were evaluated by the following charge-discharge test.

[0137] The battery was charged at a rate of 0.1 C until the voltage reached 4.25 V (vs. Li), and then cut off at a rate of 0.05 C while maintaining the voltage at 4.25 V (vs. Li). The battery was then discharged at a rate of 0.1 C until the voltage reached 3.0 V (vs. Li) (1 st The above charge / discharge test was repeated 50 cycles, and the capacity retention rate of the discharge capacity was measured. The results are shown in Table 1 below.

[0138] Referring to Table 1, it can be seen that the all-solid-state batteries including the positive electrodes according to Examples 1 to 4 have significantly improved life characteristics compared to the all-solid-state batteries including the positive electrodes according to Comparative Examples 1 to 6. This is presumably because the positive electrodes according to the Examples include a positive electrode active material including a first coating layer including lithium carbon oxide and a second coating layer including lithium titanium oxide, thereby reducing the interfacial resistance between the sulfide-based solid electrolyte of the positive electrode active material layer and suppressing side reactions.

[0139] [Table 1]

[0140] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the following claims also belong to the scope of the present invention. [Explanation of symbols]

[0141] 1: Positive electrode active material core 3: Positive electrode active material coating layer 5: Positive electrode active material first coating layer 7: Positive electrode active material second coating layer 10: Positive electrode active material for all-solid-state batteries 20: Positive electrode active material for all-solid-state batteries

Claims

1. A core capable of reversibly absorbing and releasing lithium ions; and a coating layer formed on a surface of the core; The coating layer includes a lithium carbon oxide represented by the following Formula 1 and a lithium titanium oxide represented by the following Formula 2: Cathode active material for all-solid-state batteries: [Chemical formula 1] Li a CO b In the above formula 1, a is 0<a≦4, and b is 0<b≦4; [Chemical formula 2] Li x Ti y O 4 In the above Chemical Formula 2, x is 0.8≦x≦1.4, and y is 1.6≦y≦2.

2.

2. The coating layer includes a first coating layer and a second coating layer, each of which is arranged from a center portion of the core toward a surface of the core, The first coating layer includes a lithium carbon oxide represented by Formula 1, The second coating layer includes the lithium titanium oxide represented by the formula 2. The positive electrode active material for an all-solid-state battery according to claim 1 .

3. The coating layer is included in an amount of 0.1 to 10 parts by weight based on 100 parts by weight of the total positive electrode active material for an all-solid-state battery including both the core and the coating layer. The positive electrode active material for an all-solid-state battery according to claim 1 .

4. The lithium carbon oxide represented by Chemical Formula 1 is included in an amount of 0.1 to 1.6 parts by weight based on 100 parts by weight of the total positive electrode active material for an all-solid-state battery including both the core and the coating layer. The positive electrode active material for an all-solid-state battery according to claim 1 .

5. The lithium titanium oxide represented by Formula 2 is included in an amount of 0.1 to 1.5 parts by weight based on 100 parts by weight of the total positive electrode active material for an all-solid-state battery including both the core and the coating layer. The positive electrode active material for an all-solid-state battery according to claim 1 .

6. The lithium carbon oxide represented by Formula 1 and the lithium titanium oxide represented by Formula 2 contained in the coating layer are contained in a weight ratio of 95:5 to 25:

75. The positive electrode active material for an all-solid-state battery according to claim 1 .

7. The thickness ratio of the first coating layer to the second coating layer is 20:80 to 80:20; The positive electrode active material for an all-solid-state battery according to claim 2 .

8. The thickness of the first coating layer is 0.001 to 0.02 μm; The thickness of the second coating layer is 0.001 to 0.02 μm; The positive electrode active material for an all-solid-state battery according to claim 2 .

9. The lithium carbon oxide is Li 2 CO 3 and The lithium titanium oxide is Li 4 Ti 5 O 12 That is, The positive electrode active material for an all-solid-state battery according to claim 1 .

10. A positive electrode active material for an all-solid-state battery according to any one of claims 1 to 9; and Including sulfide-based solid electrolytes, Positive electrode for all-solid-state batteries.

11. The sulfide-based solid electrolyte is Li 2 S-P 2 S 5 , Li 2 S-P 2 S 5 -LiX (where X is a halogen element), Li 2 S-P 2 S 5 -Li 2 O., Li 2 S-P 2 S 5 -Li 2 O-LiI, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 - LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 - LiI, Li 2 S-SiS 2 -P 2 S 5 - LiI, Li 2 S-B 2 S 3 , Li 2 S-P 2 S 5 -Z m S n (where m and n are positive numbers, and Z is any one of Ge, Zn, and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 P.O. 4 , Li 2 S-SiS 2 -Li p M.O. q (wherein p and q are positive numbers, and M is one of P, Si, Ge, B, Al, Ga, and In), Li 7-x P.S. 6-x C x (where 0≦x≦2), Li 7-x P.S. 6-x B x (where 0≦x≦2) and Li 7-x P.S. 6-x I x (where 0≦x≦2), The positive electrode for an all-solid-state battery according to claim 10.

12. The sulfide-based solid electrolyte is Li 6 P.S. 5 Cl, Li 6 P.S. 5 Br and Li 6 P.S. 5 I is an argyrodite-type solid electrolyte containing one or more selected from I; The positive electrode for an all-solid-state battery according to claim 10.

13. positive electrode; A negative electrode; and a solid electrolyte layer disposed between the positive electrode and the negative electrode; The positive electrode comprises the positive electrode for an all-solid-state battery according to claim 10. All-solid-state battery.

Citation Information

Patent Citations

  • Coated active material, and lithium solid-state battery

    WO2012160698A1

  • Cathode coating

    WO2022056039A1

  • KR2010-0120153

  • KR2018-0076132